Tumor infiltrating lymphocytes and PD-L1 expression in pre- and post-treatment breast cancers in the SWOG S0800 Phase II neoadjuvant chemotherapy trial - Pelekanou, Vasiliki (Mol Cancer Ther, 2018)
Our aim was to examine the association of pre-treatment tumor infiltrating lymphocyte (TIL) count and PD-L1 levels with pathologic complete response (pCR) and assess immune marker changes following treatment in tumor specimens from the S0800 clinical trial which randomized patients to bevacizumab+nab-paclitaxel followed by doxorubicin/cyclophosphamide (AC) versus two control arms without bevacizumab (varying sequence of AC and nab-paclitaxel). TILs were assessed in 124 pre- and 62 post-treatment tissues (including 59 pairs). PD-L1 was assessed in 120 pre- and 43 post-treatment tissues (including 39 pairs) using the 22C3 antibody. Baseline and treatment-induced immune changes were correlated with pCR and survival using estrogen receptor (ER) and treatment adjusted logistic and Cox regressions, respectively. At baseline, the mean TIL count was 17.4% (17% had zero TIL, 9% had ≥50% TILs). Post-treatment, mean TIL count decreased to 11% (5% had no TIL, 2% had > 50% TILs). In paired samples, the mean TILs change was 15% decrease. Baseline PD-L1 was detected in 43% of cases (n=5 in tumor cells, n=29 stroma, n=18 tumor+stroma). Post-treatment, PD-L1 expression was not significantly lower, 33%. Higher baseline TIL count and PD-L1 positivity rate were associated with higher pCR rate even after adjustment for treatment and ER status (p=0.018). There was no association between TIL counts, PD-L1 expression and survival due to few events. In conclusion, TIL counts, but not PD-L1 expression, decreased significantly after treatment. Continued PD-L1 expression in some residual cancers raises the possibility that adjuvant immune checkpoint inhibitor therapy could improve survival in this patient population.